Banjir dan Bantuan di Surakarta : Filantropi dalam Banjir Solo Tahun 1966 - Kholidah, Nur Isnaini (UIN Raden Mas Said Surakarta, 2022)
ABSTRACT This research discussed aboute the philanthropic practices that occurred in the Solo flood in 1966. The city of Solo and the surrounding area is an area that is often subject to flooding. This happens because Solo City is one of the areas crossed by the Bengawan Solo River, where Bengawan Solo is the longest river in Java Island. If at any time there is a significant increase in rainfall and for a long time, the worst risk caused is the occurrence of a flood disaster. One of the major floods that hit Solo City and the surrounding area was the flash flood that occurred in 1966. The incident hit six inner districts and caused considerable losses. The problem studied this time is how the philanthropic practices of the Indonesian people remain intertwined in the midst of unstable political conditions, because 1966 was a fairly crucial period. To conduct this research, the author used the historical research method. This method includes the selection of titles, data collection, criticism or selection and filtering of data, interpretation or interpretation of the data that has been obtained, and the last step is historiography or the stage of writing history. In addition to using historical research methods, the author also uses the concept of social roles as a theoretical basis in carrying out the research. The concept was chosen by the author because it is able to help the author in seeing how the role of each individual and group in the recovery of the Solo City Area and its surroundings after the flash flood disaster. The results of this reseach is explain how the flood disaster that hit the Solo region and its surroundings in 1966 could move a sense of humanity and empathy among the Indonesian people in the midst of unstable political conditions. Until the people of Solo City and also the surrounding areas who are victims of the disaster can bounce back from the slump caused by the flood disaster. The participation of the Indonesian people as a reaction to the flood event that hit Solo and its surroundings was able to restore the state of Solo City and the surrounding area as before. Keywords: Bengawan Solo, flood, philanthropy